Novel micro/nano scale characterisation of interfaces in multi-material additive manufacturing (3D-printing) - Quach, Tien Thuy (2024)
Additive manufacturing (AM) or 3D-printing has many applications in automotive, engineering, healthcare, aerospace, defence, and in the current work. Multi-material additive manufacturing is the combination of different materials within a print to enhance the performance of a component and/or final product. Although AM in its various forms allows for the use of a wide range of materials, not all of them are compatible with each other. This can be problematic when designing interfaces that need to connect or overlap parts in complex geometric products.